2017
DOI: 10.1007/s11420-016-9516-6
|View full text |Cite
|
Sign up to set email alerts
|

Open Wedge Distal Femoral Osteotomy: Accuracy of Correction and Patient Outcomes

Abstract: Opening wedge lateral DFO is a reliable procedure for the treatment of valgus knee malalignment with or without arthritic changes in the lateral compartment. Deformity correction is accurate, and patient outcomes reveal significant improvement after surgery. Longer follow-up is required to access the survivorship of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
1
28
0
1
Order By: Relevance
“…In summary, the clinical results of our cohort are comparable to those studies, who reported reliable results on LOWDFO [57, 16]. As a difference to former studies, our cohort includes especially younger patients as discussed above (for example Elattar at al.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In summary, the clinical results of our cohort are comparable to those studies, who reported reliable results on LOWDFO [57, 16]. As a difference to former studies, our cohort includes especially younger patients as discussed above (for example Elattar at al.…”
Section: Discussionsupporting
confidence: 85%
“…As a difference to former studies, our cohort includes especially younger patients as discussed above (for example Elattar at al. (range 22 to 72 years) [7], Jacobi at al. (46 + −3.1 years) [4], Dewilde et al (range 30 to 51 years) [16], and Saithna et al (range 28 to 58 years) [6]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the problems of close‐wedge osteotomy is the accuracy of correction. The surgeon is very reliant on the preoperative plan for the accuracy of bony resection; even so, precise resection of a wedge is technically difficult during surgery. Besides, shortening of the limb will increase with the enlargement of the correction angle.…”
Section: Discussionmentioning
confidence: 99%